Examining the Effectiveness of Dialectical Behavior Therapy on Impulsivity, Emotion Regulation, Rumination, and Self-Criticism in Individuals with Trichotillomania - Karimi Imam Vardikhan, Shahrbano; Hassanzadeh, Ramezan; Emadian, Seyedeh Olia (Health Nexus, 2024)
Trichotillomania is a mental disorder characterized by recurrent and irresistible urges to pull out hair from the body. The present study aimed to elucidate the effectiveness of dialectical behavior therapy on impulsivity, emotion regulation, rumination, and self-criticism in individuals with trichotillomania. From an objective standpoint, this study is considered applied research and, methodologically, a quasi-experimental study with a pre-test, post-test, and follow-up test design, including a control group with a 2-month follow-up period. The population of this research included all individuals with trichotillomania in districts 2 and 4 of Tehran, from whom 18 persons for each group were selected through purposive non-random sampling and were randomly assigned to either the experimental or control group. The instruments used in this research included the Massachusetts Hair Pulling Questionnaire, Williams and colleagues’ (1997) Emotion Regulation Scale, Barratt and colleagues’ (1990) Impulsivity Scale, Gilbert and colleagues’ (2004) Self-Criticism Scale, and Nolen-Hoeksema and colleagues’ (1991) Rumination Scale. The dialectical behavior therapy intervention was conducted over 8 one-hour sessions; however, the control group did not receive any intervention. The research was analyzed through mixed ANOVA (with repeated measures) and Bonferroni follow-up tests using SPSS version 22. The results of the present study indicated that dialectical behavior therapy has a significant effect on impulsivity (P<0.01), emotion regulation (P<0.01), rumination (P<0.01), and self-criticism (P<0.01), and these effects continue in the follow-up phase. It can be concluded that dialectical behavior therapy is effective in reducing impulsivity, improving emotion regulation, decreasing rumination, and reducing self-criticism, and can therefore be beneficial for individuals with trichotillomania.